PRINCIPLES OF LANGUAGE POLITENESS IN SPEECH ACTS OF MADRASAH ALIYAH DARUL IHSAN MAKASSAR TEACHERS IN LEARNING AND TEACHING ACTIVITIES - Abd. Rahman Rahim (INFOKUM, 2022)
Language is a mirror of its speakers. Whatever the information delivered by the educator or discussed by the students, it is highly likely to be accepted and comprehended by others if the educators' and students' language is acceptable to the listeners or readers. This study intends to evaluate the principles of politeness in speech acts, identify types of speech acts, and describe Madrasah Darul Ihsan Makassar teachers' departures from the rules of politeness in speech acts in learning. The methodology employed is qualitative, and the sort of research is descriptive. Sources of information derived from the speech acts of teachers instructing diverse courses and classes. The results indicated that Madarasah Aliyah teacher Darul Ihsan Makasasar utilized the principle of politeness in language using six maxims: the maxim of wisdom, the maxim of consensus, the maxim of appreciation, the maxim of simplicity, the maxim of generosity, and the maxim of sympathy. The Madrasah Aliyah instructor, Darul Ihsan Makassar, employs the maxim of sympathy in the teaching and learning process. The instructor at Madrasah Aliyah Darul Ihsah Makassar uses directive, representational, expressive, and declarative speech acts in her instruction.